BIO-ANALYTICAL DETERMINATION OF CLOPIDOGREL AND PANTOPRAZOLE BY RP-HPLC METHOD IN RAT PLASMA: APPLICATION TO DRUG INTERRACTION STUDY - GURUPADAYYA, B.M.; SAMA, SINDHURA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To develop simple, sensitive, rapid, robust and reproducible method for the bioanalytical determination of clopidogrel and pantoprazole in rat plasma using reverse phase high performance liquid chromatographic method. Method: The analysis was performed on C8 (250 × 4.6mm, 5μm) column with a mobile phase consisting of 0.03M potassium dihydrogen ortho phosphate buffer (pH 3), acetonitrile in the ratio of 40:60 (v/v) with a flow rate of 1.2 ml/min. The analyte was monitored with UV detector at 240 nm. In the developed method pantaprazole elutes at retention time of 2.6 min and clopidogrel at 8.2 min. Results: The proposed method is having linearity in the concentration range 10-50 µg/ml for both clopidogrel and pantoprazole. The method was validated with respect to system suitability, linearity, precision, limit of detection (LOD) and limit of quantification (LOQ), accuracy (recovery), ruggedness, robustness, stability, forced degradation studies (specificity). The method is extended to animal study. The pharmacokinetic parameters (AUC,Cmax,Tmax) was found statistically significant(p<0.05). Conclusion: The results suggest that concomitant use of clopidogrel and pantaprazole alters pharmacokinetics of clopidogrel. Key Words: Bio-Analytical, Clopidogrel, Pantoprazole, RP-HPLC Method, Rat Plasma, Drug Interaction Study